Sustainable Procedures of Corporate Social Responsibility - Werner Güth; Hartmut Kliemt (Philipps-University Marburg, School of Business and Economics, 2021)
Directly non-profit-seeking CSR strategies can be indirectly profitable and sustainable provided their presence can be detected by other actors with sufficient reliability at sufficiently low costs. This creates a niche for implementing CSR procedures in ways that are compatible with shareholder approaches to responsible corporate governance. Though ethical norms of equal interpersonal respect for all stakeholders are appealing, spelling them out in concrete procedural terms renders them ethically less attractive than they appear in theory. If ethical ideals of equal respect for all stakeholders in CSR do not have the extreme implications laid out here where are the alternatives?
Keywords: 330; Equal Ethical Respect; Corporate Social Responsibility; Obliquity; Shareholder and Stakeholder Conceptions